OTONOMI PENGELOLAAN KEUANGAN PADA PERGURUAN TINGGI NEGERI BADAN HUKUM - Ryan Surya Pradhana (Jurnal Hukum Peratun, 2021)
After promulgation of The Law of Republic Indonesia No. 12 Year 2012 on Higher Education, State College with Legal Entity (PTN-BH) has an authority to conduct its own institutional management which is not only academic autonomy, but also non-academic autonomy too, where that financial management autonomy is included. For this reason, this paper was made in order to examine the extent of financial management autonomy in PTN-BH. The writing method used in this research is a normative juridical approach using a statutory approach and a conceptual approach. This paper uses the legal-normative method, namely an approach based on legal materials by examining concepts, theories, legal principles, and legislation, as well as literature related to writing. It is found in this writing that the PTN-BH’s autonomy of financial management is distributed by delegation authority scheme based on PTN-BH statute. One of critical point from the regulation is the separation of PTN-BH’s wealth of the country’s wealth which is cause a genuine legal concequences on various aspect.